Terpenoid glycosides from the root's barks of Eriocoelum microspermum Radlk. ex Engl. (August 2018) - Pertuit, David; Mitaine-Offer, Anne-Claire; Miyamoto, Tomofumi; Tanaka, Chiaki; Delaude, Clément; Lacaille-Dubois, Marie-Aleth
Abstract: Eight undescribed triterpenoid saponins together with a known one, and two undescribed sesquiterpene glycosides were isolated from root's barks of Eriocoelum microspermum . Their structures were elucidated by spectroscopic methods including 1D and 2D experiments in combinaison with mass spectrometry as 3- O -α-L-rhamnopyranosyl-(1 → 3)-[α-L-rhamnopyranosyl-(1 → 2)]-α-L-arabinopyranosylhederagenin, 3- O -α-L-rhamnopyranosyl-(1 → 3)-[β-D-glucopyranosyl-(1 → 3)-α-L-rhamnopyranosyl-(1 → 2)]-α-L-arabinopyranosylhederagenin, 3- O -α-L-rhamnopyranosyl-(1 → 3)-[β-D-xylopyranosyl-(1 → 3)-α-L-rhamnopyranosyl-(1 → 2)]-α-L-arabinopyranosylhederagenin, 3- O -α-L-rhamnopyranosyl-(1 → 4)-[α-L-rhamnopyranosyl-(1 → 2)]-α-L-arabinopyranosylhederagenin 28- O -β-D-glucopyranosyl ester, 3- O -α-L-rhamnopyranosyl-(1 → 3)-β-D-xylopyranosyl-(1 → 4)-β-D-xylopyranosyl-(1 → 3)-α-L-rhamnopyranosyl-(1 → 2)-α-L-arabinopyranosylhederagenin, 3- O -α-L-rhamnopyranosyl-(1 → 3)-α-L-arabinopyranosyl-(1 → 4)-β-D-xylopyranosyl-(1 → 3)-α-L-rhamnopyranosyl-(1 → 2)-α-L-arabinopyranosylhederagenin, 3- O -β-D-xylopyranosyl-(1 → 4)-α-L-arabinopyranosyl-(1 → 4)-β-D-glucopyranosyl-(1 → 3)-α-L-rhamnopyranosyl-(1 → 2)-α-L-arabinopyranosylhederagenin, 3- O -α-L-rhamnopyranosyl-(1 → 4)-α-L-rhamnopyranosyl-(1 → 3)-α-L-arabinopyranosyl-(1 → 4)-β-D-glucopyranosyl-(1 → 3)-α-L-rhamnopyranosyl-(1 → 2)]-α-L-arabinopyranosylhederagenin, 1- O -β-D-xylopyranosyl-(1 → 3)-[α-L-rhamnopyranosyl-(1 → 2)]-β-D-glucopyranosyl-(1 → 4)-α-L-rhamnopyranosyl-(1 → 6)-[β-D-xylopyranosyl-(1 → 3)]-[α-L-rhamnopyranosyl-(1 → 2)]-β-D-glucopyranosyl-(2E, 6E)-farnes-1-ol, 1- O -β-D-glucopyranosyl-(1 → 3)-[α-L-rhamnopyranosyl-(1 → 2)]-β-D-glucopyranosyl-(1 → 4)-α-L-rhamnopyranosyl-(1 → 6)-[β-D-xylopyranosyl-(1 → 3)]-[α-L-rhamnopyranosyl-(1 → 2)]-β-D-glucopyranosyl-(2E, 6E)-farnes-1-ol. These results represent a contribution to the chemotaxonomy of the genus Eriocoelum highlighting farnesol glycosides as chemotaxonomic markers of the subfamily of Sapindoideae in the family of Sapindaceae. Graphical abstract: Phytochemical investigations of the root's barks of Eriocoelum microspermum (Sapindaceae) led to the isolation of eight undescribed triterpene saponins, and two acyclic sesquiterpene glycosides. There structures were established by spectroscopic methods. The sesquiterpene glycosides are considered as good chemotaxonomic markers of the subfamily Sapindoideae. Image 1 Highlights: Eight undescribed triterpene glycosides were isolated from Eriocoelum microspermum. Two undescribed sesquiterpene glycosides were purified from E. microspermum. Structures were determinated by spectroscopic methods. Chemotaxonomic significance of the sesquiterpene glycosides is discussed.